MARKET STRUCTURE OF MALAYSIAN PALM OIL REFINING INDUSTRY - Choo Sze Yi,; Alias Radam,; Azman Hassan,; Mad Nasir Shamsudin, (Asian Academy of Management Journal, 2018)
Palm oil refining industry has become one of the most important industries in Malaysia since 1960s. In the second quarter of 2018, total production and total exports of Malaysian palm oil products recorded low-single digit drop, despite an encouraging recovery in production in 2017. It is worrying to note the declining trend of utilisation rate of these refineries over the years signifying the loss of market share of these refineries in the global market. This study aims to focus on determining the structure of the industry using six concentration indicators namely Herfindahl-Hirschman index (HHI), concentration ratio (CR), entropy index (EI), relative entropy (RE), Hannah and Kay index (HKI), and the Gini coefficient (GINI). The results obtained indicate that the industry is an oligopoly with apparent shift from a highly indexed oligopoly to a lower indexed oligopoly during the studied period. The results further affirmed the concern raised in this study that the domestic palm oil refining industry has lost its market share and position in the international market.